LEMBAGA KEUANGAN MIKRO SYARIAH: EKSISTENSI DAN AKSESIBILITASNYA BAGI PEMBIAYAAN USAHATANI DI SUMATERA BARAT (Studi Kasus: Koperasi Jasa Keuangan Syariah (KJKS) Baitul Maal Wat Tamwil (BMT)) - Widya Fitriana (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
Farm financing is one of the factors facilitating the development of agriculture which allow farmers to expand the scale of farming and adopt new technologies. Unfortunately, a number of financial institutions often perceive farmers as